(3GdfcJ aj GdYbGFO GdcdGejI GdEeGejIs - (3eMeO Hf eMeO Hf GdfYeGf Hf YHO GdSdGe GdYcHQqj, CHh YHO Gddg, GdeajO, hjYQa HGHf GdeYde , J (B413 (3g`s ((3eMeO Hf WGgQ GdSeGhi s)
(3ChdgG (B:s
(3hHYO agPg YbjOI bGOfi GdOdjd EdjgG hbhi GYJeGOi YdjgG LYdJgG ai ZGjI GdJhVjM hQJHJgG Ydi NeSI aUhd s
(3BNQgG (B:s
(3ajchf eG CNHQ Hg GdfHi Udi Gddg Ydjg hSde MbkG dPdc fLRJ GdfcJ s
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3BjI Gddg GdMcje GdYGeI (B_ (3GdfLa (B(998) s
Keywords: (3GdJhMjO hGdedd hGdfMds